POLICY MODELONMARINE TOURISM DEVELOPMENT IN WAKATOBI REGENCY (SE SULAWESI,INDONESIA) - Yulius, -; Heriati, Aida; Salim, Hadiwiijaya Lesmana; Purbani, Dini; Ramdhan, Muhammad (Marine Research in Indonesia, 2015)
Wakatobi Regency has a huge capacity in natural resources with its beautiful and pristine coastalÂ ecosystems that host 25 coral reefs species in diverse forms. The regency is considered as the worldâs bestÂ biosphere and frequently visited by local and international tourists for diving/snorkeling. The objectives of this study are to determine the role of marine tourism in Wakatobiâseconomy and formulate an appropriate and strategic policy for its marine tourism development plan. Methods used in this research are theLocation Quotient (LQ) analysis to determine the relative ability of a sub-area to a wider area in the specific sector, and theProspective Participatory Analysis for preparing the marine tourism development plan. The LQ analysis for the marine tourism (trade, hotels, and restaurants) sector based on GDP data from 2004-2007 shows values ranging from 0.808-0.881, which indicate poor potential and low contribution of this sector toWakatobiâs economy. TheProspective Participatory Analysis involving 18 variables related to marine tourism development indicates that Wakatobi Regency has four key variables. These are:community behavior towards environmental protection, community character, human resources andmotivation. These variables would play an important role in preparing and implementing marine tourism development plan in Wakatobi Regency.